FROM ANXIETY TO ADAPTABILITY: RECONSTRUCTING CAREER RATIONALITY THROUGH COGNITIVE BEHAVIORAL THERAPY (CBT): A SYSTEMATIC REVIEW - Alfikriah, Syahira; Hidayah, Nur; Wahyuni, Fitri; Prabawa, Abi Izzatur (Counsenesia Indonesian Journal Of Guidance and Counseling, 2025)
Cognitive Behavioral Therapy (CBT) is increasingly being applied in the context of career guidance and counseling in response to the growing phenomenon of career anxiety and uncertainty in the BANI (Brittle, Anxiety-inducing, Non-linear, and Incomprehensible) era. This study examines the contribution of CBT in helping individuals transition from a state of career anxiety to more rational thinking and stronger career adaptability. The study was conducted using the Systematic Literature Review (SLR) method on nine articles obtained from the Google Scholar and Publish or Perish databases with the criteria of publications in English and Indonesian in the period 2015–2025. The results show that the consistent application of CBT improves self-efficacy, career maturity, and career adaptability in various population groups, including students and professionals. CBT has been proven effective in reducing career anxiety through cognitive restructuring, strengthening self-control, and developing reflective and realistic thinking patterns about one's career future. In addition, CBT also strengthens the four main dimensions of career adaptability concern, control, curiosity, and confidence which form the basis of psychological resilience in facing changes in the world of work. Based on these findings, this study confirms that the integration of CBT into career guidance services is an effective strategy for shaping a generation that thinks rationally, is adaptive, and is resilient in facing career dynamics in the BANI era.